Mechanical Modeling of the Human Cricoid Cartilage Using Computer-Aided Design: Applications in Airway Balloon Dilation Research. (January 2016) - Johnson, Christopher M.; Howell, John T.; Mettenburg, Donald J.; Rueggeberg, Frederick A.; Howell, Rebecca J.; Postma, Gregory N.; Weinberger, Paul M.
Objectives: Balloon dilation is generally considered first-line treatment for airway stenosis. Some dilation systems utilize a compliant balloon that can conform around rigid structures. Others use a noncompliant balloon that does not conform, allowing for dilation of more rigid stenoses. We hypothesized that subglottic dilation with a noncompliant balloon increases the likelihood of fracture of the cricoid when compared to a compliant balloon. Methods: Three fresh human cricoid cartilages were placed in a universal testing system to determine the expansile force necessary for cricoid fracture. Using these data, a 3D printer was used to construct a synthetic cricoid model possessing near identical physical characteristics to the human cricoid. Simulated dilation was then performed on the model using a compliant and a noncompliant balloon. Results: Human cricoid fracture occurred at 97.25 N (SD = 8.34), and the synthetic cricoid model fractured at 100.10 N (SD = 7.32). Both balloons fractured the model in every replicate experiment. Mean balloon internal pressure at fracture was 7.67 ATM (SD = 1.21) for the compliant balloon and 11.34 ATM (SD = 1.29) for the noncompliant balloon. Conclusions: These data show that fracture of the cricoid is a valid concern in balloon dilation procedures where the balloon spans the subglottis. Furthermore, the hypothesis was rejected in that the compliant balloon system was at least as likely to fracture the cricoid model as the noncompliant.